Survey Techniques to Measure and Explain Corruption - Reinikka, Ritva; Svensson, Jakob (World Bank, Washington, DC, 2014)
Reinikka and Svensson demonstrate that, with appropriate survey methods and interview techniques, it is possible to collect quantitative micro-level data on corruption. Public expenditure tracking surveys, service provider surveys, and enterprise surveys are highlighted with several applications. While often broader in scope, these surveys permit measurement of corruption at the level of individual agents, such as schools, health clinics, or firms. They also permit the study of mechanisms responsible for corruption, including leakage of funds and bribery, as data on corruption can be combined with other data collected in these surveys.